2021
DOI: 10.1051/sicotj/2021041
|View full text |Cite
|
Sign up to set email alerts
|

Superior functional outcome with dual mobility THR as compared to conventional THR in fracture neck femur: a prospective cohort study

Abstract: Introduction: Total Hip Replacement (THR) in displaced Fracture Neck of Femur (FNOF) is associated with higher dislocation rates. Conventional THR with a large femoral head and anterior approach has reduced the instability, but it remains higher than THR done for other aetiology. Recent studies have shown reduced dislocation rates with dual mobility THR (DMTHR) for FNOF; however, there is a lack of comparative research to show its superiority over conventional THR. Further, its role in the Asian subcontinent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In view of this emerging new evidence, we chose to perform DMC THA in this cohort of patients (patients<55 years of age) with stage 4 Ficat-Arlet AVN of the hip. Studies by Agarwala S et al and Agarwala Sanjay et al 26,27 have demonstrated an excellent track record of the implant type used in our study. Both these studies reported excellent patient reported outcome measure (Harris Hip Score).…”
Section: Discussionsupporting
confidence: 63%
“…In view of this emerging new evidence, we chose to perform DMC THA in this cohort of patients (patients<55 years of age) with stage 4 Ficat-Arlet AVN of the hip. Studies by Agarwala S et al and Agarwala Sanjay et al 26,27 have demonstrated an excellent track record of the implant type used in our study. Both these studies reported excellent patient reported outcome measure (Harris Hip Score).…”
Section: Discussionsupporting
confidence: 63%
“…Fifty-two patients were treated with DM and 51 patients were treated with FB. There was no dislocation occurred in both groups, but the range of motion was significantly better in DM group (21) . Comparing the series of dual mobility cups in the treatment of displaced fractures of the femoral neck to recent series of bipolar hemiarthroplasties, the relative risk of dislocation appears 4-4.7 times higher for hemiarthroplasties.…”
Section: Discussionmentioning
confidence: 76%
“…The objectives of this design are to reduce wear and loosening forces, to use a physiological system and to increase joint range without compromising intra-prosthetic stability [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…A review of comparative results, where the main parameter to be evaluated is stability, showed that dual mobility cups have excellent short and medium term results compared to standard implants in pTHR [22].…”
Section: Discussionmentioning
confidence: 99%